2019
DOI: 10.1016/j.ejvs.2019.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Editor's Choice – The Impact of Endovascular Aneurysm Repair on Long Term Renal Function Based on Hard Renal Outcomes

Abstract: This study assessed renal decline in patients who have undergone elective endovascular aneurysm repair (EVAR) over the long term (nine years of follow up), based on estimated glomerular filtration rate (eGFR). It appears that patients undergoing EVAR exhibit a significant loss of eGFR over the long term and this is associated with poor survival. This information is important for decision making when selecting patients suitable for EVAR, especially younger patients, and also for guiding follow up in this high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Several observational studies have shown that CKD (eGFR <60 ml/min per 1.73 m 2 ) before surgery is associated with greater post-operative eGFR decline 59 and higher odds of eGFR loss >20% during long-term follow-up. 60,61 Similarly, CKD has been associated with higher 30-day and long-term mortality, higher risk of cardiovascular events, and longer length of hospital stay after AAA surgery (Figure 2). 62,63 Diagnostic evaluation and post-surgery follow-up of AAA in patients with CKD Duplex ultrasonography, computed tomographic angiography, and magnetic resonance angiography are commonly used for diagnosis of AAA.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Several observational studies have shown that CKD (eGFR <60 ml/min per 1.73 m 2 ) before surgery is associated with greater post-operative eGFR decline 59 and higher odds of eGFR loss >20% during long-term follow-up. 60,61 Similarly, CKD has been associated with higher 30-day and long-term mortality, higher risk of cardiovascular events, and longer length of hospital stay after AAA surgery (Figure 2). 62,63 Diagnostic evaluation and post-surgery follow-up of AAA in patients with CKD Duplex ultrasonography, computed tomographic angiography, and magnetic resonance angiography are commonly used for diagnosis of AAA.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Furthermore, the evolution of glomerular filtration rates was not a criterion collected during the design of the study, which prevents conclusions on this important point, when recent results suggest that patients undergoing EVAR may experience a significant long term decrease in renal function. 37 Moreover, 81.8% of the centres included fewer than 10 patients per year in the study. Access to the overall number of endograft implantations performed in those centres is not available, but it is reasonable to think that some of them did not perform 10 EVAR cases per year, and performed even fewer EVAR cases per year with this specific endograft.…”
Section: Limitationsmentioning
confidence: 99%
“…AKI after F/BEVAR was found to be associated with decreased short-and long-term survival [299], although, it rarely results in permanent renal dysfunction as both sCr concentration and GFR returned to baseline by 6 months after the procedure as described by Wang et al [300]. Charles et al confirm higher mortality with eGFR loss at long term over a median of 9 years following EVAR, and observed long-term decrease of renal functions in some of the pts [301]. Gombert et al Investigated open repair for type II TAAAs if anatomically feasible [298].…”
Section: Renal Failure As a Complicationmentioning
confidence: 92%